Penerapan Mobilisasi Dini Terhadap Penurunan Skala Nyeri Pada Pasien Post Sectio Caesarea - Khimayasari, Ika Nor; Mualifah, Laily (Borobudur Nursing Review, 2023)
Abstract Background: Cesarean section (CS) is the process of delivering a baby through surgical incisions in the abdominal and uterine walls. The World Health Organization (WHO) reported 2016 that the rate of deliveries through CS increased by 10%-15%. In the region of Yogyakarta Special Region (DIY) in 2018, the CS rate reached 23.06%, and at the Wonosari Regional General Hospital, it reached 993 cases. This procedure gives rise to nursing issues such as pain, leading to discomfort and limited mobility. One non-pharmacological technique used to alleviate pain is early mobilization. Objective: This case study aims to describe the implementation of early mobilization in reducing pain scale among post-cesarean section patients. Method: This case study employs a descriptive method. Data collection was conducted from March 21-23, 2023, using interviews and observations as data collection methods. The instruments used include pain scale observation sheets and the Standard Operating Procedure (SOP) for early mobilization. Results: The application of early mobilization for 3 days managed to reduce the pain scale from 6 to 2. Conclusion: From this case study, it can be concluded that the implementation of early mobilization effectively reduces the pain scale among post-cesarean section patients. Keywords: Post Cesarean Section, Pain, Early Mobilizati Abstrak Latar Belakang : Sectio caesarea (SC) yaitu proses mengeluarkan janin melalui tindakan pembedahan dinding perut dan dinding rahim. WHO (Word Health Organization) mengatakan pada tahun 2016 tingkat persalinan dengan metode SC meningkat 10%-15%. Di DIY 2018 mencapai 23,06%, sedangkan di RSUD Wonosari mencapai 993 kasus. Tindakan ini menimbulkan masalah keperawatan yaitu nyeri yang mengakibatkan rasa tidak nyaman dan keterbatasan gerak. Salah satu teknik nonfarmakologi yang digunakan untuk mengurangi nyeri yaitu mobilisasi dini. Tujuan : Studi kasus ini bertujuan untuk menggambarkan penerapan mobilisasi dini terhadap penurunan skala nyeri pada pasien post sectio caesarea. Metode : Studi Kasus ini menggunakan metode deskriptif. Pengambilan data dilaksanakan pada tanggal 21-23 Maret 2023. Metode pengumpulan data yang digunakan yaitu wawancara dan observasi. Instrument yang digunakan yaitu lembar observasi skala nyeri dan Standar Operasional Prosedur (SOP) mobilisasi dini. Hasil : Penerapan mobilisasi dini selama 3 hari mampu menurunkan skala nyeri dari 6 menjadi 2. Kesimpulan : Dari studi kasus ini penerapan mobilisasi dini mampu menurunkan skala nyeri pada pasien post sectio caesare. Kata Kunci : Post Sectio Caesarea, Nyeri, Mobilisasi dini